THE DEVELOPMENT OF SOCIAL IDENTITY STRATUM IN HENRIK IBSEN’S A DOLL HOUSE: A NEW PERSPECTIVE TO IDENTITY - Eslmieh, Razieh (PEOPLE: International Journal of Social Sciences, 2017)
Based on Bakhtin’s theories of dialogism and stratification, the paper suggests that individual identity is not unified, is not a complete whole, and is not static rather identity with its diverse strata is dynamic, developing and evolving. Gender identity, cultural identity, linguistic identity, imposed identity, ideological identity, spacial identity, national identity, racial identity, topographical identity and even diverse sorts of hybrid identities such as socio-political identity, socio-linguistic, socio-cultural are just some strata of individual’s nonhomogeneous identity. For matters of space and time, the present paper seeks to prove the existence of social identity based on Alfred Adler’s theory of Individual Psychology and the concepts of superiority complex and inferiority complex and their representative causes such as social interest, style of life, and masculine protest. Looking from a different angle, the paper discusses superiority and inferiority complexes as the building blocks of social identity. Moreover, social interest, style of life, and masculine protest are the forming factors of the complexes and henceforth the stratum of social identity. The theories are applied on Henrik Ibsen’s A Doll House to study the development and suppression of social identity in Nora which lead her to seek her released un-imposed identity. Released un-imposed identity is interpreted in power structure relations as dissident or rebellious identity.